Risk assessment of petroleum-contaminated soil using soil enzyme activities and genotoxicity to Vicia faba - Ma, Jun (Ecotoxicology (London, England), 2014)
Pollution caused by petroleum is one of the most serious problems worldwide. To better understand the toxic effects of petroleum-contaminated soil on the microflora and phytocommunity, we conducted a comprehensive field study on toxic effects of petroleum contaminated soil collected from the city of Daqing, an oil producing region of China. Urease, protease, invertase, and dehydrogenase activity were significantly reduced in microflora exposed to contaminated soils compared to the controls, whereas polyphenol oxidase activity was significantly increased (P < 0.05). Soil pH, electrical conductivity, and organic matter content were correlated with total petroleum hydrocarbons (TPHs) and a correlation (P < 0.01) existed between the C/N ratio and TPHs. Protease, invertase and catalase were correlated with TPHs. The Vicia faba micronucleus (MN) test, chromosome aberrant (CA) analyses, and the mitotic index (MI) were used to detect genotoxicity of water extracts of the soil. Petroleum-contaminated samples indicated serious genotoxicity to plants, including decreased index level of MI, increased frequency of MN and CA. The combination of enzyme activities and genotoxicity test via Vicia faba can be used as an important indicator for assessing the impact of TPH on soil ecosystem